2020
DOI: 10.25259/sni_610_2020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic antegrade aqueductoplasty and stenting with panventricular catheter in management of trapped fourth ventricle in patients with inadequately functioning supratentorial shunt

Abstract: Background: Trapped fourth ventricle (TFV) usually develops as a complication of supratentorial ventricular CSF shunting, especially when hydrocephalus is caused by intraventricular hemorrhage and/or infection. This study aimed to assess the feasibility of endoscopic aqueduct stenting using a single refashioned shunt tube to treat cases presenting with both TFV and shunt malfunction. Methods: We retrospectively collected and analyzed data from patients presenting with TFV and supratentorial shunt malfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…He proposed an aim in such cases to minimize the number of surgeries (endoscopic/shunt procedures). Another study[ 11 ] has assessed a refashioned multiperforated catheter in management of 18 patients with trapped fourth ventricle, reporting good neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…He proposed an aim in such cases to minimize the number of surgeries (endoscopic/shunt procedures). Another study[ 11 ] has assessed a refashioned multiperforated catheter in management of 18 patients with trapped fourth ventricle, reporting good neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than fourth ventricular shunting as the most widely used technique, many treatment modalities for isolated fourth ventricles were developed including direct microsurgical ventriculocisternostomy (19,20) . Endoscopic approaches include endoscopic fenestration, aqueductoplasty, aqueductal stenting, and cysto-ventricular fenestration with or without shunting (21,22) . Some authors favored a direct microsurgical opening of the outlet of the fourth ventricle, avoiding the insertion of a fixed foreign body, as the preferred primary surgical option for entrapment of the fourth ventricle (23) .…”
Section: Modalities Of Treatmentmentioning
confidence: 99%
“…Some authors reported the use of the cranial endoscope in the management of trapped 4 th ventricle by inserting the ventricular catheter antegrade from the lateral ventricle through the aqueduct to the 4 th ventricle under endoscopic visualization so that draining both supra and infratentorial ventricular system via single Kochar valve. They concluded that this is a valid option only with clear anatomic landmarks in the supratentorial ventricular system together with short aqueductal stenosis (22) . Ventriculocisternostomy: Although posterior 4 th ventricular fenestration to the subarachnoid space seems to be a valid alternative option when endoscopy is not feasible, still it is major surgery with posterior fossa craniotomy that may carry cranial surgery complications.…”
Section: Th Ventricular Catheter and Y Connectormentioning
confidence: 99%
“…2 When neuroimaging show progression or when symptoms of brainstem compression are present, surgery is highly recommended. [2][3][4][5][6][7][8] Considering this etiology, it is not uncommon that some patients present symptomatically to the hospital during an episode of shunt malfunction. In those patients with ventricular size enlargement, the shunt malfunction can provide a suitable scenario for the cotreatment of IFV by performing an endoscopic aqueductoplasty with a single panventricular catheter using a precoronal approach.…”
mentioning
confidence: 99%
“…
Endoscopic aqueductoplasty with stent is an effective surgical technique for isolated fourth ventricle (IFV) treatment. [1][2][3][4][5][6][7][8][9][10] This condition is more frequently observed in shunted patients after postmeningitic or posthemorrhagic hydrocephalus of preterm infants. 2 When neuroimaging show progression or when symptoms of brainstem compression are present, surgery is highly recommended.
…”
mentioning
confidence: 99%